Metoder för att beskriva kumulativa effekter med avseende på biologisk mångfald och vägar - Rodéhn, Johan (SLU/Dept. of Landscape Architecture, Planning and Management (from 130101), 2004)
Cumulative effects are seldom treated in Swedish Environmental Impact Assessments (EIA). This report treats these questions and which procedures and methods that can be used when assessing cumulative effects in EIA.